Branchless Banking: Service Innovation Through Additive Models and Transformational Models at Bank Syariah Indonesia - Hana, Kharis Fadlullah; Mustaqim, Bagus Sirot (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2023)
The presence of digital banks currently provides new challenges for conventional banks. Bank operations are required to adapt to technological developments. If the customer cannot follow it, the bank will be abandoned by the customer. The purpose of this study is to explore the innovations made by Indonesian Sharia Banks in dealing with digital bank attacks. Digital services through Additive models and transformational models have been carried out, but the results are not optimal. This study uses interview data sourced from managers and frontliners of Indonesian Sharia Banks. This research approach uses a qualitative method with a case study strategy. The results of this study indicate that in optimizing branchless banking, Indonesian Sharia Banks provides account opening services through mobile banking. Another finding is that Indonesian Islamic Banks use the Gardening Strategy. The recommendation from this research is to improve branchless banking services through BSI Smart.